Optimization of Energy Consumption in WSN Based on PSO - et. al., Palak Keshwani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research, we are proposing new protocols for energy used in wireless networks. We are optimizing energy usage based on Improved Particle Swarm Optimization (PSO) integrated with conventional Ad-hoc On Demand Distance Vector (AODV) used to generate the minimum amount of cluster heads (CHs) and the objective work involves two main components. First, the total energy used between the cluster head and the nodes; second the total energy used to collect data at the cluster head level as well as to transfer the information to the base station. Thus, in order to achieve energy efficient cooperative transmission, we are providing a new approach and applying to transmit the data to the suitable next node of the cluster far from the head of the previous cluster in the clustered head sensor network.